The noodle maker of Kalimpong : the untold story of my struggle for Tibet - Rgya-lo-don-grub, Lha-sras, 1928-; Thurston, Anne F. (PublicAffairs, 2015)
In December 2010 residents of Kalimpong, a town on the Indian border with Tibet, turned out en masse to welcome the Dalai Lama. It was only then they realized for the first time that the neighbor they knew as the noodle maker of Kalimpong was also the Dalai Lama's older brother. The Tibetan spiritual leader had come to visit the Gaden Tharpa Choeling monastery and join his brother for lunch in the family compound. Gyalo Thondup has long lived out of the spotlight and hidden from view, but his whole life has been dedicated to the cause of his younger brother and Tibet. He served for decades as the Dalai Lama's special envoy, the trusted interlocutor between Tibet and foreign leaders from Chiang Kai-shek to Jawaharlal Nehru, Zhou Enlai to Deng Xiaoping. Traveling the globe and meeting behind closed doors, Thondup has been an important witness to some of the epochal events of the 20th century. No one has a better grasp of the ongoing great game as the divergent interests of ...